Exploring the Relationship between Human Resource Management Practices and Organizational Commitment: Empirical Evidence from the Banking Sector in China - Ghazanfar, Faheem; ., Muhammad Siddique; ., Mohsin Bashir (Information Management and Business Review, 2012)
The purpose of this paper is to measure the impact of human resource management practices individually and as a system on organizational commitment. Data were collected from 304 respondents from banking sector of China. A questionnaire survey for this purpose was conducted in different cities of China. Correlations and multiple regression statistics analysis were used to explore the relationship between the variables involved in the study. The findings of the study provide support for the variables (selection, training, performance appraisal, promotion, performance based rewards, information sharing, job security and human resource management system) and are confirmed by the results of the previous studies. The findings of the current study support the notion that the HR practices relates to organizational commitment, individually and as a system as well. These findings provide important avenues for the banking sector of China and for the debate regarding convergence of the human resource management practices regionally as well as internationally.